1986
DOI: 10.1161/01.atv.6.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of endothelial cell shape and wall shear stress in a stenosed dog aorta.

Abstract: The pattern of endothelial geometry at various locations along stenosed dog aortas was examined. This was done to test the hypotheses that the shape of an endothelial cell is related to the local wall shear stress associated with the flowing blood and that alterations in hemodynamics, produced by vascular geometrical changes, influence endothelial cell geometry. Aortic stenosis with a reduction of 71% of the cross-sectional area was produced. The animals were sacrificed 12 weeks later, and the endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
128
1
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(137 citation statements)
references
References 34 publications
6
128
1
2
Order By: Relevance
“…The effects of shear stress on endothelial cells have been investigated in various studies. Although there is no study that directly investigates the relationship between shear stress and the fraction of leaky junctions, there have been studies on the effect of shear stress on cell shape (4,17,27), proliferation rate (12, 41), and hydraulic conductivity and permeability (27,28). Levesque et al (17) observed a stenosed dog aorta and correlated the cell shape with levels of shear stress.…”
mentioning
confidence: 99%
“…The effects of shear stress on endothelial cells have been investigated in various studies. Although there is no study that directly investigates the relationship between shear stress and the fraction of leaky junctions, there have been studies on the effect of shear stress on cell shape (4,17,27), proliferation rate (12, 41), and hydraulic conductivity and permeability (27,28). Levesque et al (17) observed a stenosed dog aorta and correlated the cell shape with levels of shear stress.…”
mentioning
confidence: 99%
“…In areas of uniform laminar flow, endothelial cells exhibit an ellipsoidal cell (and nuclear) shape and alignment in the direction of flow, whereas in regions of disturbed flow, this orderly pattern is disrupted. 8,9 In addition, arterial wall remodeling (eg, after experimental surgical coarctation or shunting procedures) appears to depend at least in part on a functionally intact endothelium. 10 Direct evidence that hemodynamic forces can influence endothelial structure and function has come from studies in which cultured endothelial cells have been subjected to defined fluid mechanical forces under well controlled conditions in vitro.…”
mentioning
confidence: 99%
“…It has been shown that endothelial cells undergo morphological alterations in response to changes in the degree and orientation of shear stress, with elongated endothelial cells that are located in regions of high shear stress having their long axes aligned parallel to the direction of flow and polygonal endothelial cells in low shear stress regions being aligned in haphazard directions. 46 -47 It has been postulated by Asakura and Karino 22 that these alterations may be responsible for the changes in endothelial cell permeability to atherogenic lipoprotein particles. Yoshizumi et al 48 have recently shown that low shear stress stimulates the expression of endothelin mRNA and the release of endothelin into the culture medium from cultured porcine endothelial cells.…”
mentioning
confidence: 99%